Strategi Pengelolaan Sumber Daya Keuangan untuk Meningkatkan Akses dan Kualitas Pendidikan di Daerah 3T: Systematic Literature Review - Anisah Fardila; Hamidatul Khalifah; Maya Diaz Restarie; Unifah Rosyidi; Muh. Takdir (Journal on Education, 2025)
This study aims to analyze financial resource management strategies in order to improve access and quality of education in the Frontier, Outermost, and Disadvantaged (3T) regions in Indonesia. The 3T region faces various challenges, such as limited infrastructure, shortage of educators, and limited access to learning facilities. This study uses a qualitative approach with a literature study method. Data were obtained through in-depth studies and analysis of policy documents related to the education budget. The results of the discussion indicate that effective financial resource management can improve access and quality of education in the 3T region. The implementation of this strategy can reduce the gap in access and improve the quality of learning. This study recommends strengthening collaboration between the central and regional governments and non-governmental organizations to ensure effective and sustainable financial management in the 3T region. Optimal financial resource management in the 3T region is expected to achieve greater access to education and better quality education.